EVALUASI PELAKSANAAN PEMBANGUNAN INFRASTRUKTUR JALAN KABUPATEN DI KABUPATEN KENDAL (Studi Kasus Pembangunan Infrastruktur Jalan Kabupaten di Desa Cening, Kecamatan Singorojo) - Haqiqi, Brilliant Nauval; Manar, Dzunuwanus Ghulam; Herawati, Nunik Retno (Journal of Politic and Government Studies, 2024)
Infrastructure development is an important thing that is carried out for the smooth running of the national or regional development process. One of the infrastructures that is the concern of the government is the road, because the infrastructure can encourage the smooth mobility of people, goods, and services. Kendal Regency government is addressing the problems of road infrastructure development in the region, especially district roads. One of the problematic kabuaten roads in Kendal Regency is in Cening Village, Singorojo District because it has been damaged for 35 years. The research method used by the researcher in carrying out this research is qualitatively descriptive, with data collection in the form of interviews, observations, and documentation. Researchers use qualitative methods because they want to find out and analyze in depth related to how Development Management, inhibiting factors, and solutions to complete the existing district roads in Cening village, where the road section has long been in a damaged condition. The main speakers in this study were the Public Works and Spatial Planning Office of Kendal Regency and the Cening village government. This study uses the management theory of George R. Terry that includes planning, organizing, executing, and supervising. The concept is used in the process of development of district road infrastructure in Cening Village. However, in the process of road construction, there are several obstacle factors that will be evaluated using the concept of Bridgman & Davis with indicators in the form of inputs, processes, outputs, and outcomes. On the other hand, the Regency Road in Cening village has not been completely built one hundred percent, but still leaves the Cening-Kaliputih road section which is still in a badly damaged condition. Therefore, the Cening village government felt the need to report back and inquire about the news of the certainty of the construction of the Cening-Kaliputih road to the relevant parties. Furthermore, the Kendal Regency government through the Kendal Regency DPUPR must also be able to solve the problem of damaged roads in Kendal Regency in general and Cening village in particular.